2004
DOI: 10.1074/jbc.m311842200
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Isotopomer Analysis of Anaplerotic Pathways in INS-1 Cells

Abstract: Anaplerotic flux into the Kreb's cycle is crucial for glucose-stimulated insulin secretion from pancreatic ␤-cells. However, the regulation of flux through various anaplerotic pathways in response to combinations of physiologically relevant substrates and its impact on glucose-stimulated insulin secretion is unclear. Because different pathways of anaplerosis generate distinct products, they may differentially modulate the insulin secretory response. To examine this question, we applied 13 C-isotopomer analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 27 publications
12
141
3
Order By: Relevance
“…13 C labeling and isotopomer analysis is an effective methodology to quantify fluxes in mammalian metabolic pathways, as evidenced by several research articles and reviews [41][42][43][44][45][46][47][48][49][50][51][52]. There has been increasing emphasis on comprehensive isotopomer balancing, global optimization, and meticulous selection of a 13 C carbon source mixture [28,30,33,36] in the accurate interpretation of 13 C labeling data and evaluation of fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…13 C labeling and isotopomer analysis is an effective methodology to quantify fluxes in mammalian metabolic pathways, as evidenced by several research articles and reviews [41][42][43][44][45][46][47][48][49][50][51][52]. There has been increasing emphasis on comprehensive isotopomer balancing, global optimization, and meticulous selection of a 13 C carbon source mixture [28,30,33,36] in the accurate interpretation of 13 C labeling data and evaluation of fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…15 Tandem mass spectroscopy provides an advantage over high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection in that each purine nucleotide is monitored by unique ion pairs, thereby minimizing artifactual signals from co-eluting metabolites. Viability mixtures and time course samples were centrifuged at 175 ×g for 4 minutes at 4°C and the supernatant was aspirated.…”
Section: Electrospray Tandem Mass Spectroscopy (Lc/ms/ms) Analysis Ofmentioning
confidence: 99%
“…The rate of pyruvate carboxylation correlates with the glucose concentration applied to pancreatic islets and thus is correlated with the rate of insulin secretion [5]. 13 C-NMR isoprotomer studies of glucose metabolism in clonal cell lines have also shown a correlation between insulin secretion and pyruvate flux through the pyruvate carboxylase reaction [8,9]. The purpose of anaplerosis in the beta cell is different from that in many other tissues which possess a high level of pyruvate carboxylase.…”
Section: Introductionmentioning
confidence: 99%